The complete mitochondrial genome of common redshank (Tringa totanus) - Jianying Ren; Xue Jiang; Liang Dou; Lin Yan; Xuelian Zhang; Xiuyue Zhang (Mitochondrial DNA. Part B. Resources, 2019)
Tringa totanus is declining throughout Europe and performing protection in China. In this study, we sequenced the complete mitochondrial genome using PCR method. It is the first published complete mitochondrial genome of T. tetanus, which is a circular molecule of 16,818 bp, and it contains 13 typical vertebrate protein-coding genes, 22 tRNA, and two rRNA. The phylogenetic tree was constructed to validate the taxonomic status of T. totanus, exhibiting it a closer relationship to T. glareola.